2013
DOI: 10.1095/biolreprod.112.102640
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Plasmid Therapy Results in Long-Lasting High Circulating Lh and Increased Sperm Production in European Sea Bass (Dicentrarchus labrax)1

Abstract: The present work aimed at evaluating the potential of intramuscular injection of a hormone-coding gene as an approach for gene therapy in fish. A plasmid containing luteinizing hormone (Lh) in a single-chain (sc) form, pCMV-scLh, was chosen as the coding gene, and sea bass was chosen as the target species. In vivo injection of pCMV-scLh in muscle of juvenile sea bass rendered plasma Lh levels higher than 50 ng/ml in 40% of the injected fish, while these Lh levels were only detected in 4% of controls. Injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
1
10
1
Order By: Relevance
“…Furthermore, the second increase in Fsh (a minor peak), which occurs in early spermatogenesis, produced higher plasma levels in large fish than in small ones, suggesting a supportive role of this hormone to Lh during the final stages of gametogenesis. Similarly, during spermiation, large fish showed higher Lh levels than small fish (the main peak), which is in agreement with the well-known role of Lh in the final stages of gametogenesis (Rodríguez et al, 2000(Rodríguez et al, , 2005Felip et al, 2008;Rocha et al, 2009;Carrillo et al, 2010;Mazón et al, 2013). Finally, large fish showed a small, yet significant peak in Lh during early gametogenesis that was not present in small fish, and which has been previously described .…”
Section: Small and Large Fish Endocrinologysupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the second increase in Fsh (a minor peak), which occurs in early spermatogenesis, produced higher plasma levels in large fish than in small ones, suggesting a supportive role of this hormone to Lh during the final stages of gametogenesis. Similarly, during spermiation, large fish showed higher Lh levels than small fish (the main peak), which is in agreement with the well-known role of Lh in the final stages of gametogenesis (Rodríguez et al, 2000(Rodríguez et al, , 2005Felip et al, 2008;Rocha et al, 2009;Carrillo et al, 2010;Mazón et al, 2013). Finally, large fish showed a small, yet significant peak in Lh during early gametogenesis that was not present in small fish, and which has been previously described .…”
Section: Small and Large Fish Endocrinologysupporting
confidence: 90%
“…Large fish during the early and final stages of gametogenesis displayed higher hormone levels than small fish. The absence of these peaks in small fish leads to reproductive failure (Based on Espigares et al, 2015a;Molés et al, 2011Molés et al, , 2012Mazón et al, 2013Mazón et al, , 2014Rodríguez et al, 2000Rodríguez et al, , 2005Felip et al, 2008;Rocha et al, 2009;Carrillo et al, 2010).…”
Section: Screening Studies To Determine a Photosensitive Periodmentioning
confidence: 99%
“…Presumably, as observed for single-chain Lh [17], the bioavailability of scFsh in the bloodstream would take longer in the animals injected with plasmid than in those directly injected with the hormone; therefore, the experiment was prolonged one more week in the case of the plasmid-treated groups. Fish were sampled weekly, after anesthesia with ethylene glycol-monophenyl ether (0.5 ml/L water).…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Our previous studies using plasmid DNA injections in sea bass skeletal muscle have demonstrated the ability of this tissue to incorporate and express the injected gene [16]. Moreover, injection of a plasmid encoding a single-chain Lh resulted in the production of the blood-secreted recombinant Lh, which had physiological effects on milt production in adult sea bass [17].…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish and trout, Fsh has no effect on testicular gsdf expression (García-Ló pez et al 2010, Sambroni et al 2013a), but in our study Fsh strongly stimulated (approximately fivefold) the expression of this gene. In sole, the concomitant Fsh-mediated increase in gsdf and the apparently antagonist gene amh remains intriguing, since in other teleosts Fsh and androgens strongly inhibit amh expression (Miura et al 2002, García-Ló pez et al 2010, Mazó n et al 2013, Rolland et al 2013, Sambroni et al 2013a. The specific role of amh during sole spermatogenesis is currently unknown, and therefore it is possible that this gene is required for germ cell proliferation as has been proposed for medaka (Oryzias latipes) during early gonadal differentiation (Shiraishi et al 2008).…”
Section: Fsh Mainly Controls the Expression Of Growth Factors In Sertmentioning
confidence: 99%